Altered Contralateral Auditory Cortical Morphology in Unilateral Sudden Sensorineural Hearing Loss - Fan, Wenliang (Otol Neurotol, 2015)
OBJECTIVE: To investigate the cerebral gray matter volume alterations in unilateral sudden sensorineural hearing loss patients within the acute period by the voxel-based morphometry method, and to determine if hearing impairment is associated with regional gray matter alterations in unilateral sudden sensorineural hearing loss patients. STUDY DESIGN: Prospective case study. SETTING: Tertiary class A teaching hospital. PATIENTS: Thirty-nine patients with left-side unilateral sudden sensorineural hearing loss and 47 patients with right-side unilateral sudden sensorineural hearing loss. INTERVENTION: Diagnostic. MAIN OUTCOME MEASURE: To compare the regional gray matter of unilateral sudden sensorineural hearing loss patients and healthy control participants. RESULTS: Compared with control groups, patients with left side unilateral sudden sensorineural hearing loss had significant gray matter reductions in the right middle temporal gyrus and right superior temporal gyrus, whereas patients with right side unilateral sudden sensorineural hearing loss showed gray matter decreases in the left superior temporal gyrus and left middle temporal gyrus. A significant negative correlation with the duration of the sudden sensorineural hearing loss (R = −0.427, p = 0.012 for left-side unilateral SSNHL and R = −0.412, p = 0.013 for right-side unilateral SSNHL) was also found in these brain areas. There was no region with increased gray matter found in both groups of unilateral sudden sensorineural hearing loss patients. CONCLUSIONS: This study confirms that detectable decreased contralateral auditory cortical morphological changes have occurred in unilateral SSNHL patients within the acute period by voxel-based morphometry methods. The gray matter volumes of these brain areas also perform a negative correlation with the duration of the disease, which suggests a gradual brain structural impairment after the progression of the disease.